2012
DOI: 10.1186/1746-6148-8-114
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus interferes with MHC class I surface expression by targeting vesicular transport and Golgi

Abstract: BackgroundThe Orf virus (ORFV), a zoonotic Parapoxvirus, causes pustular skin lesions in small ruminants (goat and sheep). Intriguingly, ORFV can repeatedly infect its host, despite the induction of a specific immunity. These immune modulating and immune evading properties are still unexplained.ResultsHere, we describe that ORFV infection of permissive cells impairs the intracellular transport of MHC class I molecules (MHC I) as a result of structural disruption and fragmentation of the Golgi apparatus. Depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Orf virus (a parapox virus) causes disruption and fragmentation of golgi in Vero cells. This structural modification affects the late vesicular export machinery and results in downregulation of the host immune response [127]. Similar phenomenon was also reported upon expression of 3C protease of foot-and-mouth disease virus in Vero cells [128].…”
Section: Effect On the Morphology Of Golgi Bodysupporting
confidence: 69%
“…Orf virus (a parapox virus) causes disruption and fragmentation of golgi in Vero cells. This structural modification affects the late vesicular export machinery and results in downregulation of the host immune response [127]. Similar phenomenon was also reported upon expression of 3C protease of foot-and-mouth disease virus in Vero cells [128].…”
Section: Effect On the Morphology Of Golgi Bodysupporting
confidence: 69%
“…These cells interact to form a barrier to invasion and provide the basis of highly integrated local dermal defence system ( Jenkinson et al, 1991). Rohde et al (2012) showed that ORFV down-regulates MHC I surface expression in infected cells by targeting the late vesicular export machinery and the structure and function of the Golgi apparatus, which possibly helps to escape cellular immune recognition. Plasmacytoid dendritic cells are involved in the immunological protective response against Orf infection (Saadeh et al, 2014).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…One the one hand, the protein of interest can be directly investigated by using protein-specific antibodies and (confocal laser scanning) fluorescence microscopy as e.g. shown for Golgi-localized proteins [43]. Many researchers use proteins fused to GFP or RFP reporters to visualize their intracellular traffic directly [3].…”
Section: Discussionmentioning
confidence: 99%